2019
DOI: 10.1371/journal.pone.0221978
|View full text |Cite
|
Sign up to set email alerts
|

Distraction of olfactory bulb-medial prefrontal cortex circuit may induce anxiety-like behavior in allergic rhinitis

Abstract: Allergic rhinitis is a chronic inflammatory disease of the upper respiratory tract, which is associated with high incidence of anxiety symptom. There is evidence that medial prefrontal cortex modulates anxiety-related behaviors and receives projections from olfactory bulb. Since olfactory dysfunction has been reported in allergic rhinitis, we aimed to evaluate anxiety-like behavior and oscillations of olfactory bulb-medial prefrontal cortex circuit in an animal model of allergic rhinitis. The number of open ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 53 publications
(52 reference statements)
2
27
0
Order By: Relevance
“…Release of factors from local immune-cells or infected mucosa cells may provide a potential mechanism of communication between infected/inflamed nasal tissue and brain. 51 , 52 , 53 , 54 , 55 Similar observations of host response to combat viral entry were made for other viruses that enter via the olfactory system. 56 , 57 , 58 Therefore, it is important to compare our observations with other respiratory virus infections, such as influenza to enable identification of SARS-CoV-2 specific effects.…”
Section: Discussionsupporting
confidence: 56%
“…Release of factors from local immune-cells or infected mucosa cells may provide a potential mechanism of communication between infected/inflamed nasal tissue and brain. 51 , 52 , 53 , 54 , 55 Similar observations of host response to combat viral entry were made for other viruses that enter via the olfactory system. 56 , 57 , 58 Therefore, it is important to compare our observations with other respiratory virus infections, such as influenza to enable identification of SARS-CoV-2 specific effects.…”
Section: Discussionsupporting
confidence: 56%
“…2013 ; Salimi et al. 2019 ). After successful establishment of the model, the rats in the blank group and model group were given normal saline in nasal cavity every day.…”
Section: Methodsmentioning
confidence: 99%
“…Thirty rats were randomly divided into 3 groups. All groups, except the blank control group, were injected with ovalbumin OVA (purchased from Sigma) and aluminum-containing adjuvant to initiate allergic rhinitis model according to the previously described method (Liu et al 2013;Salimi et al 2019). After successful establishment of the model, the rats in the blank group and model group were given normal saline in nasal cavity every day.…”
Section: Allergic Rhinitis Animal Models In Vivomentioning
confidence: 99%
“…There have been no other animal studies on AR-related depression in recent years. However, some animal studies on abnormal brain responses secondary to nasal immune-inflammatory responses after AR have been reported, and it has been suggested that brain regions such as hippocampus, cortex, and olfactory bulb are closely related to the development of mental disorders in AR animals (35)(36)(37). Along with the achievements in animal model studies, some authors have also conducted relevant experiments using blood samples and cells from depressed patients and AR patients, and confirmed the correlation between the neurotransmitter 5-hydroxytryptamine and the cytokines secreted by T lymphocytes during an allergic reaction (38).…”
Section: Causes and Mechanisms Of Depression In Armentioning
confidence: 99%